Analisis Pebandingan Pengukuran Kinerja Perbankan Dengan Metode CAMEL Dan RGEC (Studi Pada Perusahaan Perbankan Umum Swasta Devisa Yang Terdaftar Di Bursa Efek Indonesia tahun 2017-2019) - Ratna Kumala; N. Rachma; Budi Wahono (E-JRM : Elektronik Jurnal Riset Manajemen, 2021)
AbstractThe Purpose of this study is to compare banking performance using the CAMEL and RGEC methods, in private foreign exchange commercial banks listed on the IDX for three periods, namely in 2017-2019 using purposive sampling, 15 samples were obtained that met the sample selection criteria. This study is a descriptive study. with a qualitative approach. The data collection technique in this research is by examining company records or documents. The analysis used is the CAMELS and RGEC methods by determining the soundness of a bank to be a bank's soundness rating. The results showed that the assessment of the health of private foreign exchange public banking using the CAMELS method on average showed the predicate Unwell. And foreign exchange private commercial banks that use the RGEC method on average show a Quite Healthy predicate. So that the performance of foreign exchange private public banks should pay more attention to the company's external factors that affect financial performance, so that companies can improve their company's financial performance. Keywords: CAMELS, RGEC, banking soundess level.